Design and Implementation of an IDA-PBC for a Grid Connected Inverter used in a Photovoltaic System. Issue 1 (2018) - Barman, Saumitra; Samanta, Soumya; Mishra, Jyoti Prakash; Roy, Prasanta; Roy, Binoy Krishna
Abstract: The paper presents an interconnection damping assignment - passivity based control (IDA-PBC) strategy applied to a grid-connected inverter interfaced Photovoltaic (PV) system. The PV power plant is integrated to the grid using a pulse-width-modulated converter. This is done to extract maximum energy from the renewable resource and feed it to the grid. The main contribution of this paper is to design a nonlinear control law based on IDA-PBC with a desired energy function along with an integral action. In the design of IDA-PBC, the Hamiltonian function is considered as a Lyapunov function candidate for analysing the stability criteria. In this paper, a step by step design procedure of the IDA-PBC is presented and the performance of the controller is compared with a conventional PI-based controller. A simulation study of the system is carried out in Matlab/Simulink environment. Finally, the simulation results show that the IDA-PBC with an integral action performs better during both transient and steady state conditions as compared with the PI-based controller.